Perbandingan Metode-Metode dalam Pendugaan Evapotranspirasi Berbasis Radiasi Matahari - Tjandra, M Agita; Fadila, Salsa Nur; Yanti, Nika Rahma (Universitas Andalas, 2025)
This research aims to determine a method for estimating evapotranspiration (ET) using radiation-based methods to obtain evapotranspiration results that are close to the Penman Monteith (PM) method for the Cupak Tangah Village area, Pauh District, Padang City. This research was conducted using the Caprio, Droogers and Allen, Berti and McGuinness and Bordne methods as a comparison method to the PM method. The parameters used are weather parameters such as solar radiation, temperature, humidity, wind speed, barometric pressure and others. Based on the analysis carried out, it was found that the empirical method that approaches the Penman Monteith evapotranspiration value is the McGuinness and Bordne method with the regression equation y = 0.8601x and R2 = 0.9864. In order, the methods for estimating evapotranspiration from those that are close to those that are not close to the PM results are the McGuinness and Bordne, Caprio, Droogers and Allen, and Berti methods.